Inhibitory Effects of Digoxin and Digitoxin on Cell Growth in Human Ovarian Cancer Cell Line SKOV-3. (March 2021) - Chou, Jou-Chun; Li, Jie-Hau; Chen, Chih-Chieh; Chen, Chien-Wei; Lin, Ho; Wang, Paulus S.
Background: Cardiac glycosides (CGs) possess a chemical structure similar to steroids, and are inhibitors of the sodium potassium pump. An anti-tumor effect of CGs in breast and prostate cancers has been reported, but the effect of CGs on ovarian cancer is still unclear. Aims: In this study, the effects of CGs on proliferation, cytotoxicity and cell cycle of ovarian cancer cell line (SKOV-3) have been investigated. Procedure: The cell proliferation and cytotoxicity were detected by MTT assay and LDH activity assay, respectively. CGs, at concentrations higher than IC50, decreased cell proliferation and showed increased cytotoxicity toward SKOV-3 cells. The colony-formation ability was reduced after treatment with digoxin and digitoxin for 10 days. Furthermore, we explored the effect of digoxin and digitoxin on the distribution of cell cycle by flow cytometry. Results: Results revealed that both digoxin and digitoxin led to cell cycle arrest in G0 /G1 phase with 24 or 48 hours, but the arrest of G0 /G1 phase was not observed at 72 hours. We evaluated the percentage of hypodiploid cell population as an index of the cellular fragments through flow cytometry. The data indicated that cellular fragments were significantly increased by treating with digitoxin at the concentrations of IC50 and 10 −6  M for 72 hours. Conclusion: Taken together, these data suggest that CGs decreased cell proliferation and increased cytotoxicity through cell cycle arrest at the G0 /G1 phase. CGs have anti-tumor effect in SKOV-3 cells and might be a potential therapeutic drug for ovarian cancer. Since this study is a preliminary investigation of CGs on SKOV-3 cells, more experiments might be performed in the future. Furthermore, more ovarian cancer cell lines might also be employed in the future studies to confirm the effect of CGs in ovarian cancer.